2019
DOI: 10.2478/raon-2019-0054
|View full text |Cite
|
Sign up to set email alerts
|

Definitive radiochemotherapy in esophageal cancer - a single institution experience

Abstract: BackgroundDefinitive radiochemotherapy is the preferred treatment option in patients with the cancer of the cervical esophagus and a viable treatment option in patients with the cancer of lower two thirds of the esophagus, who decline proposed surgical treatment. The purpose of the study was to evaluate the treatment results with definitive radiochemotherapy of patients with esophageal cancer, treated in a single institution in the period from 2010 to 2017.Patients and methodsAll available medical data for 55 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“… 20 Radiotherapy is an effective treatment strategy for esophageal cancer and considerably prolongs the survival of patients. 6 , 7 , 21 Patients with esophageal cancer who are administered radiotherapy are prone to negative emotions, anxiety, and depression during treatment, which can greatly affect the postoperative recovery and prognosis, thus reducing the effectiveness of treatment and the quality of life of patients. Additionally, several studies have shown that depression and anxiety are significantly higher in patients with esophageal cancer than in the general population and in patients with other types of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 Radiotherapy is an effective treatment strategy for esophageal cancer and considerably prolongs the survival of patients. 6 , 7 , 21 Patients with esophageal cancer who are administered radiotherapy are prone to negative emotions, anxiety, and depression during treatment, which can greatly affect the postoperative recovery and prognosis, thus reducing the effectiveness of treatment and the quality of life of patients. Additionally, several studies have shown that depression and anxiety are significantly higher in patients with esophageal cancer than in the general population and in patients with other types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Radiotherapy is an effective method of treating EC and considerably prolongs the survival of patients. 6,7 However, radiotherapy has toxic side effects in patients and might also lead to malnutrition. 8 Long-term malnutrition reduces the quality of life of patients and their tolerance to radiotherapy and decreases treatment sensitivity, resulting in prolonged hospitalization or shortened survival time, or in severe cases, treatment failure due to lack of tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…7 Similarly, a large number of studies have confirmed that postoperative radiotherapy can significantly improve the OS rate and RFS rate of patients with esophageal cancer. 8 Fourth, in our opinion, tumor location should be considered in this study. Studies have shown that the survival rate of tumors located in the upper, middle, and lower esophagus is different, the prognosis of upper esophageal cancer is worse than that of middle esophagus and lower esophagus.…”
Section: Effect Of Perioperative Flurbiprofen Axetil On Long-term Survival Of Patients With Esophageal Carcinoma Who Underwent Thoracoscomentioning
confidence: 93%